Study on the quality of work life towards employees work engagement at Kubang Pasu district council Jitra, Kedah / Nur Mashidayu Zakaria - Zakaria, Nur Mashidayu (Faculty of Business Management, Universiti Teknologi MARA, 2016)
This purpose of this study is to study on the Quality of Work Life towards Employee's Work Engagement. The scope of the study involved permanent staff at Kubang Pasu District Council. The data of this study were gathered through the distribution of questionnaires and using simple random sampling techniques. In this study, the data collected were analyzed by using Statistical Package for Social Science (SPSS) software version 20.0. Based on the findings, the result identified that there was a relationship between the element in Quality of Work Life and employees work engagement. Researcher highly recommends on the element in Quality of Work Life play a role in order to achieve work engagement at Kubang Pasu District Council. From the entire independent variable in QWL, "safe and healthy working condition" was discovered as the most influential element in QWL while "adequate and fair compensation" was the least influential element. Researcher also wishes that there will be a study conducted in the future using other element in Quality of Work Life to know whether they carry the same result.